Experimental evaluation of UWB wireless communication within PC case - Gelabert, J; Edwards, D; Stevens, C (2011)
A novel concept of the use of an ultra-wide bandwidth (UWB) ultra-small-scale wireless interconnect scheme inside an electrically small enclosure is proposed. The concept is presented using a PC tower case as a model environment in which a channel measurement campaign has been made with two different types of antennas. Ricean K factor analysis was conducted for different positions of the antennas to identify the multipath behaviour of the channel, as well as channel capacity. An average maximum channel capacity of almost 6Gbit/s is achieved using the whole UWB band for one of the antennas, assuming a signal-to-noise ratio of 25dB. This work supports the proposal that a high-capacity UWB wireless interconnect scheme for communicating different devices within a PC case scenario may be used to replace wired interconnections, providing a wireless backplane system. © 2011 The Institution of Engineering and Technology.